Prinsip Kehati-hatian bagi Bank Selaku Kustodian di Pasar Modal Indonesia - Rezandha Hutagalung (Jurnal Suara Hukum, 2020)
This journal aims to find out how to apply the precautionary principle of a bank as a custodian bank in Indonesian capital market. Whereas with the enactment of Law Number 1995 concerning the Capital Market, it is deemed necessary to enact a Bapepam Decision regarding the Custodian Bank's Report. In the context of carrying out Indonesia's economic development, of course the challenges are not insignificant for financial institutions, one of which is in banking institutions. The role of banking institutions that carry out the main task as a vehicle that can collect and distribute funds effectively and efficiently, requires continuous improvement in order to be able to have a comparative advantage. This journal is how about the application of the precautionary principle in the capital market in Indonesia. Custodian Bank is a commercial bank that has obtained the approval of the Financial Services Authority (OJK) to carry out business activities as a custodian. The object of legal research is legal norms, which have the aim of examining whether or not a regulation is appropriated and applied.